A Exclusão Social nos Municípios e Coredes do Rio Grande do Sul Segundo o Índice Social Municipal Ampliado - Cláudio Barbieri Dias (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2003)
The Municipal Social Wide Index (Indice Social Municipal Ampliado Isma), it was built by Fundação de Economia e Estatística (FEE) starting from a wide research of available variables, being selected the mostrepresentative of the socioeconomic conditions and susceptible to annual reproduction, be for data ofadministrative registrations or own estimates, resulting in the composition of fourteen indicators, which werecontained in four blocks: Condition of Home and Sanitation; Education; Health; and Income. These blockscompose the Isma and they try to express the life conditions in all of the municipal districts of the state, and theindex vary from 0,0 to 1,0 the one that propitiates classify the municipality, of the best for the worst. Whencontained by areas, in this case, by Regional Council of Development (Coredes), they expose a scenery to level macro and diversified for the municipality, where it is visualized the social inequalities. Here we are presented theresults of Isma and their blocks for the municipality and Coredes, with the analysis of the acting of 1998 inrelation to average of the period 1991-96. Also standing out the most bad indicators. Like this, the present work pretend to be an auxiliary instrument, more complete of the life conditions in the municipality, with information updated annually, for the establishment of priorities in the public politics.